On the case of the missing detail and the twisted truth about hard work. (September 2015) - Schreven, Stephanie
This text, its politics, and erotics originate in 'the case of the missing detail': the alliance between Warner Brothers Entertainment Inc. and the author J.K. Rowling during a trial over copyright infringement and fair use concerning a lexicon, which, I argue, puts at stake, as an opportunity, ownership in the properties of the story and world of Harry Potter. During the trial, the author alone takes center stage. In investigating the alliance and making a case for its shared interests, this text brings together work and consumption. I look at the role work and specifically 'hard work' by the author plays in criminalizing and containing consumption that is disorderly, disrespectful, and excessive: consumption by fans. Fans who write fan fiction are not content to merely read and consume; they disrespect the symbolic authority of the author to write their own and different stories and create symbolic value in excess of and for the original story. However, in the end, and in this case, at stake in criminalizing and containing consumption by fans are interests that have nothing to do with hard work, but with collecting rent instead, on the license to use the Harry Potter trademark for branding. Consumption that is disorderly, disrespectful, and excessive undermines the symbolic value of the brand, embodied in a distinctive identity, and hence its attractiveness to be licensed, by diluting it. The law functions to regulate consumption as proper to secure brand value, which legally renders the story of Harry Potter undead to the imagination.